PENILAIAN RISIKO KESEHATAN KERJA PADA USAHA MIKRO KAIN PERCA - Hendrilie, Velycia; Aziza, Annisaa; Tamarifa, Zhaqina Azizah; Putri, Alya Miranti; Fitriani, Desi Nur; Jailani, M. Adji Fajar; Refra, Dian Dewi Vifani; Rizqita, Vanessa Ainum; Wulandari, Nasywa Noor; Fadilah, Hilya; Tanvie, Farnaz Keisya; Carissa, Azalia Wardhani Dya; Putri, Mauliza Kurnia; Elok, Wita; Nuriah, Hindiyati (Universitas Trisakti, 2025)
This study aims to assess occupational health risks in micro-scale patchwork fabric businesses. Data were collected through field observations and worker interviews, covering workplace characteristics, manual handling activities, health complaints, and existing control measures. The findings reveal significant health risks, including musculoskeletal disorders, symptoms related to sick building syndrome, and psychosocial stress. Workplace conditions feature low lighting, high temperatures, and inadequate humidity levels. Overburdened manual handling tasks further exacerbate health risks. Analysis was conducted by comparing field data with relevant regulations and theories, such as NIOSH and Indonesian labor regulations. This study provides recommendations to improve occupational health and safety, including ergonomics implementation, workplace environmental control, and psychosocial management.